HLA has strongest association with IgA nephropathy in genome-wide analysis. - Feehally, J; Farrall, M; Boland, A; Gale, D; Gut, I; Heath, S; Kumar, A; Peden, J; Maxwell, P; Morris, D; Padmanabhan, S; Vyse, T; et al. (2010)
Demographic and family studies support the existence of a genetic contribution to the pathogenesis of IgA nephropathy, but results from genetic association studies of candidate genes are inconsistent. To systematically survey common genetic variation in this disease, we performed a genome-wide analysis in a cohort of patients with IgA nephropathy selected from the UK Glomerulonephritis DNA Bank. We used two groups of controls: parents of affected individuals and previously genotyped, unaffected, ancestry-matched individuals from the 1958 British Birth Cohort and the UK Blood Service. We genotyped 914 affected or family controls for 318,127 single nucleotide polymorphisms (SNPs). Filtering for low genotype call rates and inferred non-European ancestry left 533 genotyped individuals (187 affected children) for the family-based association analysis and 244 cases and 4980 controls for the case-control analysis. A total of 286,200 SNPs with call rates >95% were available for analysis. Genome-wide analysis showed a strong signal of association on chromosome 6p in the region of the MHC (P = 1 × 10(-9)). The two most strongly associated SNPs showed consistent association in both family-based and case-control analyses. HLA imputation analysis showed that the strongest association signal arose from a combination of DQ loci with some support for an independent HLA-B signal. These results suggest that the HLA region contains the strongest common susceptibility alleles that predispose to IgA nephropathy in the European population.